2020
DOI: 10.20960/nh.03275
|View full text |Cite
|
Sign up to set email alerts
|

Changes in adherence to the Mediterranean diet observed in a Spanish population during confinement for the SARS-CoV-2 pandemic

Abstract: Introduction: Mediterranean diet (MD) is one of the most complete and healthy dietary models according to numerous studies. In this sense, the university stage involves a substantial change in the eating habits of young adults away from the standards associated with MD. Objective: The aim of this study is to determine the level of adherence to the MD of a university population sector, establishing relation patterns with the type of population where students reside and digital leisure habits related with video … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…Relevant to the observed self-perceived shifts towards a more balanced or a Mediterranean diet-oriented pattern, our findings are in line with other studies conducted in the Mediterranean region (Di Renzo et al, 2020;Rodríguez-Pérez et al, 2020;Rossinot et al, 2020;Sánchez-Sánchez et al, 2020;Tárraga López et al, 2020). Conversely, other web-based surveys conducted in Denmark, United Arab Emirates, Poland, and Saudi Arabia, including the International Online Survey, albeit confirming changes in eating habits during the COVID-19 pandemic, suggested an overall deterioration of diet quality (Alhusseini and Alqahtani, 2020;Ammar et al, 2020;Cheikh Ismail et al, 2020;Meister, 2020;Sidor and Rzymski, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Relevant to the observed self-perceived shifts towards a more balanced or a Mediterranean diet-oriented pattern, our findings are in line with other studies conducted in the Mediterranean region (Di Renzo et al, 2020;Rodríguez-Pérez et al, 2020;Rossinot et al, 2020;Sánchez-Sánchez et al, 2020;Tárraga López et al, 2020). Conversely, other web-based surveys conducted in Denmark, United Arab Emirates, Poland, and Saudi Arabia, including the International Online Survey, albeit confirming changes in eating habits during the COVID-19 pandemic, suggested an overall deterioration of diet quality (Alhusseini and Alqahtani, 2020;Ammar et al, 2020;Cheikh Ismail et al, 2020;Meister, 2020;Sidor and Rzymski, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Although there is no robust data yet, findings from an online international survey demonstrate shifts towards a health-compromising direction (Ammar et al, 2020). However, whether eating habits have changed towards a healthier pattern as a result of the anticipated increased consumption of homemade meals due to home confinement is still a matter of concern since the literature shows inconsistent results (Alhusseini and Alqahtani, 2020;Cheikh Ismail et al, 2020;Meister, 2020;Di Renzo et al, 2020;Rodríguez-Pérez et al, 2020;Rossinot et al, 2020;Sánchez-Sánchez et al, 2020;Sidor and Rzymski 2020;Tárraga López et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It implied the acquisition of healthy habits such as “following a diet low in saturated fat”, “limiting the consumption of sugars and sweets”, “eating 2–4 servings of fruit and 3–5 servings of vegetables a day”, or “limiting the salt intake”. However, when analyzing adherence to the Mediterranean diet using the MEDAS questionnaire, both groups increased their adherence to this diet, as did the general population in many countries during the COVID-19 pandemic [ 7 , 8 ], progressing from a low to a medium adherence. However, the IG achieved a clinically significant improvement [ 57 ] on the MEDAS score of 40%, compared to 26% for the CG, with a moderate effect size, reaching a score close to 10, which corresponds to the high adherence category [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a negative impact, the number of hours per day sitting has increased between 23.8–28.6% [ 2 , 3 , 4 , 5 , 6 ], and physical activity (PA) levels have decreased by 28.8–38% [ 4 , 6 , 7 ], Dietary habits have also been affected. Even if the adherence to the Mediterranean diet has increased slightly [ 6 , 7 , 8 ], the prevalence of snacking and the consumption of alcoholic and carbonated drinks has also increased [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the impact of low-nickel diet, we found an improvement in almost all anthropometric indices already after 15 days. Recently, Tárraga López et al explored the usual dietary pattern prior to confinement and assessed the adherence to the Mediterranean diet in 490 Spanish adults without evidence of clinically relevant changes in body composition [41]. A recent Italian online survey by Maffoni et al demonstrated a slight but significant increase in BMI during the COVID-19 pandemic and stratification by lifestyle changes revealed a significant variation in BMI: negative lifestyle changes were correlated with increased BMI and positive lifestyle changes with decreased BMI [42].…”
Section: Discussionmentioning
confidence: 99%